The human microbiome and metabolomics: Current concepts and applications. Issue 16 (2nd November 2017) - Daliri, Eric Banan-Mwine; Wei, Shuai; Oh, Deog H.; Lee, Byong H.
ABSTRACT: The mammalian gastrointestinal tract has co-developed with a large number of microbes in a symbiotic relationship over millions of years. Recent studies indicate that indigenous bacteria are intimate with the intestine and play essential roles in health and disease. In the quest to maintain a stable niche, these prokaryotes influence multiple host metabolic pathways, resulting from an interactive host–microbiota metabolic signaling and impacting strongly on the metabolic phenotypes of the host. Since dysbiosis of the gut bacteria result in alteration in the levels of certain microbial and host co-metabolites, identifying these markers could enhance early detection of diseases. Also, identification of these metabolic fingerprints could give us clues as to how to manipulate the microbiome to promote health or treat diseases. This review provides an overview of our current knowledge of the microbiome and metablomics, applications and the future perspectives.